Preparation and absolute configuration of (1R,4R)-(+)-oxo-, (1S,4S)-(-)-3-oxo-and (1R,3S,4R)-(+)-3-acetyloxy-5-oxo-1,8-cineole - Loandos, Maria del Huerto (2009)
Enantiomerically pure (1S,4S)-(-)-3-oxo-1,8-cineole (-)-2 and (1R,4R)-(+)-3-oxo-1,8-cineole (+)-2 were prepared for the first time and their absolute configurations assigned by vibrational circular dichroism (VCD) measurements. Thus, treatment of cineole 1 with chromyl acetate gave rac-2 which after sodium borohydride reduction and acetylation provided racemic 3-endo-acetyloxy-1,8-cineole, rac-4. Enantioselective hydrolysis using porcine liver esterase (PLE) gave a mixture of 3-endo-hydroxy-1,8-cineole (-)-3 and 3-endo-acetyloxy-1,8-cineole (+)-4. After chromatographic separation, (-)-3 was oxidized to (+)-2, while (+)-4 was hydrolysed to (+)-3 and then oxidized to (-)-2. The absolute configuration of either ketonewas established by VCD spectroscopy in combination with density functional theory (DFT) calculations at the B3LYP/DGDZVP level of theory, from where it followed that the (+)-2 enantiomer corresponds to (1R,4R)-1,3,3-trimethyl-5-oxo-2-oxabicyclo[2.2.2]octane and the (-)-2 enantiomer to the (1S,4S) molecule which is also in agreement with the absolute configuration deduced by the Mosher method for the starting chiral alcohols. Some literature inconsistencies are clarified. In addition, the enantiomerically pure monoester (1S,3S,4R,5R)-(-)-3-acetyloxy-5-hydroxy-1,8-cineole 6 and the ketoester (1R,3S,4R)-(+)-3-acetyloxy-5-oxo-1,8-cineole 7 were prepared from meso-diacetate 5 by enantioselective asymmetrization also using PLE.